Imobilização externa com canaleta de alumínio em fraturas de rádio e ulna em cães - Pinheiro, Maicon (2009)
The main reason demanding the veterinary orthopedics services are fractures. There are several alternatives for the treatment of a fracture; however all of them aim to obtain a fast bone union, preserving the normal function of joints and soft tissues close to it. Some fractures consolidate adequately, after the correct use of a specific immobilization method, yet others result in a slower consolidation or no union. The repair of a fracture involves a sequence of cell events which evolutes since the aggression itself, formation of hematoma, starting of a plastic callus, organization of callus and recasting. It is proposed in this research, a technique for external immobilization of radio and ulna fractures in dogs. This method was used in 16 animals, patients from The Veterinary Hospital from Federal University of Santa Maria (HVU-UFSM) during the period from March 2008 to May 2009. All the patients were clinically evaluated concerning their general health conditions; after this evaluation, it was obtained the clinical-surgical diagnosis of the fracture with the help of a radiographic exam of the fractured limb. After being submitted to general anesthesia, the closed reduction of the fracture was performed, which was immobilized using an aluminum cast, made and adapted exactly to the anatomical shape of the animal s limb. Aiming to accompany the process of bone healing, the patients were submitted to radiographic control at 30, 45 and 60 days after treatment and the cast was removed when a stable bone callus was seen and there was not the line of fracture anymore. The method proposed provided the necessary conditions for the healing process, allowing, thus, the bone consolidation and the return to the patient s normal ambulation and can be used as an additional alternative to the external immobilization methods of radio and ulna fractures in dogs.